The Influence of the Use of Media Learning Raya (Cultural Variety) Based on Articulate Storyline on Interest in Learning Social Sciences for Grade IV Elementary School Students: Pengaruh Penerapan Media Pembelajaran RAYA (Ragam Budaya) berbasis Articulate Storyline Terhadap Minat Belajar IPS Siswa Kelas IV SD - Shela Ayu Pusvita Sari; Rifki Afandi (Academia Open, 2021)
This study aims to describe the effect of the Articulate Storyline Application based RAYA (Cultural Variety) Learning Media on the interest in learning social studies for fourth graders at SDN Balongmacekan, and to find out how much influence the application of the interactive articulate storyline-based RAYA (Cultural Variety) learning media has on learning interest. Social Studies students of class IV SDN Balongmacekan. Analysis of research data using the t-test (one-tail test). Uses experimental research methods and one-group pretest-posttest design. The data collection technique used a student's social studies learning interest questionnaire. The sampling technique used a total sample, and fourteen student was the fourth-grade of SDN Balongmacekan. The results showed of the t-test with a tcount of 32.56. If viewed from the t table value with a significance level of 5% (0.05), the value is 1.761, and it can be said that the value of tcount > ttable is 32.56 > 1.761. This shows an influence on applying articulate storyline-based RAYA (Cultural Variety) learning media on the interest in learning social studies for fourth-grade students at SDN Balongmacekan. While the results of the analysis using eta square show that the value of eta square is 0.987 > 0.14, this shows that there is a significant influence on the application of interactive media-based RAYA (Cultural Variety) learning media on the interest in learning social studies for fourth-grade students at SDN Balongmacekan.